2014
DOI: 10.1074/jbc.m114.578229
|View full text |Cite
|
Sign up to set email alerts
|

miR-326-Histone Deacetylase-3 Feedback Loop Regulates the Invasion and Tumorigenic and Angiogenic Response to Anti-cancer Drugs

Abstract: Background:The role of HDAC3 in anti-cancer drug resistance remains unknown. Results: HDAC3 forms a negative feedback loop with miR-326 and regulates the response to anti-cancer drugs. Conclusion: HDAC3 forms a feedback loop with multiple miRNAs to regulate the response to anti-cancer drugs. Significance: miR-326 and HDAC3 serve as targets for the development of anti-cancer therapeutics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 48 publications
2
51
0
Order By: Relevance
“…Moreover, HDAC3 and p53 have been shown to interact indirectly via formation of a complex with the MAGE-A tumour antigen, which confers resistance to chemotherapeutic agents 9 . In accordance with the above finding, downregulation of HDAC3 decreases cancer cell death in response to anticancer drugs 10 . Stimuli such as osmotic stress or FAS ligand binding trigger the caspase-7-dependent C-terminal cleavage of HDAC3 in mammalian cells, eventually leading to apoptosis induction by modulation of HDAC3 activity 11 12 .…”
supporting
confidence: 86%
“…Moreover, HDAC3 and p53 have been shown to interact indirectly via formation of a complex with the MAGE-A tumour antigen, which confers resistance to chemotherapeutic agents 9 . In accordance with the above finding, downregulation of HDAC3 decreases cancer cell death in response to anticancer drugs 10 . Stimuli such as osmotic stress or FAS ligand binding trigger the caspase-7-dependent C-terminal cleavage of HDAC3 in mammalian cells, eventually leading to apoptosis induction by modulation of HDAC3 activity 11 12 .…”
supporting
confidence: 86%
“…It has been reported that multiple lncRNAs in the SNHG family, such as SNHG1 and SNHG5, can sponge miRNAs to regulate their expression in different cancers, including prostate cancer and gastric cancer, thus participating in the tumor growth (Li et al 2017;Zhao et al 2017). In addition, miR-326 has been demonstrated to inhibit the growth of various types of tumors including HCC (Kim et al 2014;Li et al 2015b;Cao et al 2016;Wu et al 2017;Zhang et al 2017;Yin et al 2018). However, the relationship between SNHG3 and miR-326 in HCC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional Western blot analysis was performed following the methods described in a previous study [20]. The primary antibodies used included anti-Snail (1: 500, ab82846, Abcam, Cambridge, UK), anti-Vimentin (1: 2000, ab92547, Abcam) anti-E-cadherin (1: 1000, ab77287, Abcam), anti-slug (1: 1000, ab27568, Abcam), anti-P-gp (1: 2000, ab129450, Abcam), and anti-β-actin (1: 2000, ab8227, Abcam).…”
Section: Methodsmentioning
confidence: 99%